2017
DOI: 10.1186/s12882-017-0754-8
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia is an essential complication of ANCA-associated renal vasculitis: a single center cohort study

Abstract: BackgroundAnaemia is a common complication of patients with antineutrophil cytoplasmic antibody (ANCA)-associated renal vasculitis. Nevertheless, the cause and degree of such cases of anaemia have not been elucidated in detail. We aimed to investigate the prevalence, cause, pathogenesis of anaemia and the impact of anaemia on prognosis in patients with ANCA-associated renal vasculitis.MethodsWe identified 45 patients with ANCA-associated renal vasculitis that were clinically and/or histologically diagnosed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
(45 reference statements)
2
12
1
Order By: Relevance
“…We found that our study and most previous studies had similar conclusions. As a previously reported predictor ( 8 , 10 ), hemoglobin level was also identified in the present study as an important factor influencing renal survival. Different from some previous studies, the results of the present study confirmed that the urine red blood cell count was also predictive of renal survival.…”
Section: Discussionsupporting
confidence: 81%
“…We found that our study and most previous studies had similar conclusions. As a previously reported predictor ( 8 , 10 ), hemoglobin level was also identified in the present study as an important factor influencing renal survival. Different from some previous studies, the results of the present study confirmed that the urine red blood cell count was also predictive of renal survival.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, patients with matching IIF and ELISA serologies (who were more likely to receive the diagnosis of AAV) presented with lower hemoglobin levels, higher levels inflammatory markers, and higher RF levels compared to the discrepancy group. A study conducted on a small Japanese Cohort of 45 patients found that all subjects with AAV exhibited anemia which was significantly associated with the degree of renal dysfunction and life prognosis [18]. Similar results were reported by a larger international multicentric study conducted by the European Vasculitis study group, where lower hemoglobin, higher white cell count and a higher CRP to albumin ratio were found to be independent predictors of mortality for patients with AAV [19].…”
Section: Discussionsupporting
confidence: 70%
“…First, lymphocyte count may also be affected by general health and stress or various autoimmune diseases and we previously proved the lower number of lymphocyte in severe AAV compared with non‐severe AAV . Second, the reduced hemoglobin was reported to be one of systemic complication of AAV . Third, serum creatinine level is already included in BVAS as one item, and thus, it is naturally accepted that the serum level of creatinine might be correlated with BVAS well …”
Section: Discussionmentioning
confidence: 94%